2020
DOI: 10.1016/j.amsu.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The plight of COVID-19 pandemic on medical students and residency applicants

Abstract: In this pandemic situation, medical students find them in a state of apprehension. With medical institutions closed and switch to online teaching and telehealth, many aspects of medical learning are still compromised, including core clinical rotations, clinical skills evaluation, and exams cancelation. The medical students are distressed about their continuity of education and developing the necessary skill to feel confident enough to practice in the future. The involvement of medical students as frontline wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 11 publications
0
21
1
1
Order By: Relevance
“…In fact, several studies had consistently reported that medical students were concerned about approaching patients infected with unknown diseases. In such cases, it may be plausible to focus the allocation of these volunteering students to activities relating to early levels of prevention with minimum risk of exposure, including health education and promotion, contact tracing and triages, as well as peer supports for isolating patients and HCWs [ 5 , 36 , 37 ]. Contrarily, volunteering opportunity in clinical settings should be strictly limited to clinical-year students, provided that they are well-prepared and protected [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies had consistently reported that medical students were concerned about approaching patients infected with unknown diseases. In such cases, it may be plausible to focus the allocation of these volunteering students to activities relating to early levels of prevention with minimum risk of exposure, including health education and promotion, contact tracing and triages, as well as peer supports for isolating patients and HCWs [ 5 , 36 , 37 ]. Contrarily, volunteering opportunity in clinical settings should be strictly limited to clinical-year students, provided that they are well-prepared and protected [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exceptional competitiveness of the orthopedic surgery specialty, compounded with the unclear impact of COVID-19 on residency recruitment, has presented significant challenges to both applicants and programs. Since most in-person opportunities and interviews in the 2020-2021 match cycle were cancelled due to COVID-19, we anticipated that applicants would increasingly rely on residency websites to gain insight into programs and cultural fit [ 13 , 17 - 19 ]. The purpose of this study was to explore the extent to which orthopedic surgery residency websites were updated throughout the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…While it was possible to supplement inadequate information found on websites with in-person experiences in previous years, the COVID-19 pandemic has limited this year’s applicants to mostly virtual experiences. Consequently, applicants have been forced to rely more heavily on websites in the 2020-2021 application cycle [ 9 , 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taking general surgery as an example (before interviews were moved to an online format due to the COVID-19 pandemic), applicant portfolio scores were reduced the more years of postgraduate experience the applicant had at the time of applying. Currently, with self-scoring and online interviews, applicants’ self-assessment scores are divided by a number that gets higher the more years away they are from graduation, which would then decrease their overall score [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%